Dichlorobis(dibenzyl diisopropylphosphoramidite)palladium-Catalyzed Suzuki Coupling of Aryl Chlorides in N-Methyl Pyrrolidone Under Aerobic Conditions - Guo, Mengping; Wu, Xiaochun; Ge, Junying; Zhu, Zhiyong (Asian Journal of Chemistry, 2013)
The air and moisture stable dichlorobis(dibenzyl diisopropylphosphoramidite)-palladium [(PhCH2O)2P(CH3)2CHNCH(CH3)2]2PdCl2 (2) containing electron-rich, sterically bulky phosphane (1) has been successfully used in palladium-catalyzed Suzuki cross-coupling of aryl chlorides in N-methyl pyrrolidone under aerobic conditions. The corresponding coupling products were obtained in satisfactory to excellent yields.